Neonatal Mortality and Neonatal Health Services in Wad Madani Pediatric Teaching Hospital - Elrofay, Mey M.; Eljak, Imad Eldin; Miskeen, Elhadi I. (Gezira Journal of Health Sciences, 2006)
The main objectives of this study are to describe the neonatal health and neonatal health services in Wad Madani Teaching Hospital also to identify the problems which cause death. Methodology: This is a descriptive retrospective study carried   out in Wad Madani Pediatric Teaching Hospital, in a period from January to October 2003. Data was collected from hospital records; observation and interview. Results: the majority of deaths were due to prematurity 33.3%, neonatal sepsis 24.3% and birth asphyxia 20%.  The neonatal mortality (NM) to total neonatal admission from January to October 2003 was 14.6% and 41.9% of total hospital deaths. Conclusion: Our conclusions ; Neonatal death in Wad Madani Teaching Hospital was found to be significantly high , strengthening of referral system recommended and special equipments that are not available in the Wad Madani Pediatric Teaching Hospital should be provided.